The Relation of Serum High-Sensitive C- Reactive Protein to Serum Lipid Profile, Vitamin D and Other Variables in a Group of Hypertensive Patients in Erbil-Iraq (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: Hs-CRP; hypertension; lipid profile; vitamin D